Gingerbread cookie murder eaudiobook - Fluke, Joanne (Hannah Swensen Mystery, 2010)
In Joanne Fluke's "Gingerbread Cookie Murder," Hannah Swensen finds her neighbour Ernie Kusak with his head bashed in and sprawled on the floor of his condo next to an upended box of Hannah's Gingerbread Cookies - and discovers a flurry of murder suspects that is as long as her holiday shopping list. Jaine Austen, the heroine of Laura Levine's "The Dangers of Gingerbread Cookies," finds herself enlisted to help with her parents' retirement community's play "The Gingerbread Cookie That Saved Christmas". Playboy Dr. Preston McCay is playing the role of the gingerbread cookie when he "accidentally" falls to his death during the final act. Now Jaine must figure out if one of the doctor's jealous lovers was capable of murder. In "Gingerbread Cookies and Gunshots" by Leslie Meier, when Lucy Stone discovers the body of Rick Juergens, whose five-year-old son Nemo disappeared, she senses foul play. Crumbs from a gingerbread cookie Lucy gave to Nemo are found in the back seat of Rick's car. With the hours quickly ticking till Christmas, Lucy races against the clock to find a killer before he strikes again.